Tatalaksana Psoriasis Eritroderma - Prayogi Miura Susanto (Yayasan Pendidikan Medika Indonesia, 2022)
Erythrodermic psoriasis (EP) is a severe variation of psoriasis. Erythrodermic psoriasis may result from psoriasis disease or withdrawal discontinuation of previous psoriasis therapy. The pathogenesis of EP involves a wide variety of cytokines and inflammatory mediators. The diagnosis of EP was made clinically and histopathologically. Management of EP must be carried out comprehensively. Biological agents are currently more widely used as a treatment for EP and have shown good efficacy.